Production And Characterization Of Recombinant Monoclonal Antibodies Against Toxocara Antigens - Baharudeen, Zamrina Mohd (2023)
Toxocariasis is a neglected zoonotic parasitic disease caused by intestinal parasitic roundworms of dogs (Toxocara canis) and cats (Toxocara cati). Human toxocariasis has a global distribution and affects mostly people who are socioeconomically deprived. Clinicians face problems in diagnosing human toxocariasis since the signs and symptoms are non-specific and similar to other helminthic infections. Most serodiagnostic methods for toxocariasis detection rely on IgG antibody-based assays using native antigen of T. canis, however the drawback is the lack of high diagnostic specificity due to cross-reactivity with antibodies to other helminths. Additionally, IgG is a long-lasting antibody, thus IgG assays may also detect past (cured) infections. Thus, there is a need to improve the serodiagnosis of toxocariasis and one good way is by developing an antigen detection assay. To develop such an assay, recombinant monoclonal antibodies (rmAbs) to Toxocara excretory-secretory (TES) antigens can be used as the capture reagent. In this study, two recombinant proteins namely T. canis (rTES-26) and T. cati (rTES-120 cati), were expressed and purified. The isolation of mAbs to the recombinant proteins was performed via biopanning using previously produced helminth phage display immune library. Five mAbs against rTES-26 antigen were successfully isolated. However, mAbs against rTES-120 cati antigen showed incomplete scFv sequences; hence, further analysis could not be performed. Henceforth, only the mAbs of the rTES-26 antigen were characterized based on gene family, length of sequence and amino acid distribution.